A time-of-flight-based reconstruction for real-time prompt-gamma imaging in proton therapy - Jacquet, Maxime; Marcatili, Sara; Gallin-Martel, Marie-Laure; Bouly, Jean-Luc; Boursier, Yannick; Dauvergne, Denis; Dupont, Mathieu; Gallin-Martel, Laurent; Hérault, Joël; Létang, Jean-Michel; Manéval, Daniel; Morel, Christian; et al. (Physics in medicine & biology, 2021)
We propose a novel prompt-gamma (PG) imaging modality for real-time monitoring in proton therapy: PG time imaging (PGTI). By measuring the time-of-flight (TOF) between a beam monitor and a PG detector, our goal is to reconstruct the PG vertex distribution in 3D. In this paper, a dedicated, non-iterative reconstruction strategy is proposed (PGTI reconstruction). Here, it was resolved under a 1D approximation to measure a proton range shift along the beam direction. In order to show the potential of PGTI in the transverse plane, a second method, based on the calculation of the centre of gravity (COG) of the TIARA pixel detectors' counts was also explored. The feasibility of PGTI was evaluated in two different scenarios. Under the assumption of a 100 ps (rms) time resolution (achievable in single proton regime), MC simulations showed that a millimetric proton range shift is detectable at 2 with 10 incident protons in simplified simulation settings. With the same proton statistics, a potential 2 mm sensitivity (at 2 with 10 incident protons) to beam displacements in the transverse plane was found using the COG method. This level of precision would allow to act in real-time if the treatment does not conform to the treatment plan. A worst case scenario of a 1 ns (rms) TOF resolution was also considered to demonstrate that a degraded timing information can be compensated by increasing the acquisition statistics: in this case, a 2 mm range shift would be detectable at 2 with 10 incident protons. By showing the feasibility of a time-based algorithm for the reconstruction of the PG vertex distribution for a simplified anatomy, this work poses a theoretical basis for the future development of a PG imaging detector based on the measurement of particle TOF.